Students' Attitudes and Perceptions towards the Effectiveness of Field Trips Strategy in Universitas Islam Riau, Pekanbaru - rugaiyah rugaiyah (J-SHMIC : Journal of English for Academic, 2019)
This study aimed at exploring students’ attitudes and perceptions about the effectiveness of field trips strategy. The participants of this study were 40 English students of Universitas Islam Riau, Pekanbaru, Indonesia. Both qualitative and quantitative methods were applied. This study employed an exploratory mixed-method design. The questionnaire consisted of three parts and 25 items which aimed at getting information about affective learning, the qualities among students and the contribution of a field trip on Society and Individuals. A five-point Likert-scale ranging from “ strongly agree’ to “strongly disagree” was asked to respondents to be selected. While a semi-structured interviewed was used together comprehensive information about the advantages of field trips in their study. The results of this study shown that field trips contribute to students’ learning experience positively, besides it can solve many problems in the classroom and enhance the ability of students to think critically and creatively.